2020
DOI: 10.1042/bsr20200355
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal bowel movement frequency increases the risk of rectal cancer: evidence from cohort studies with one million people

Abstract: Correspondence: Zhanzhan Li (liche4006@126.com)Previous studies from case-control studies failed to draw reliable conclusions regarding the relationship between bowel movement frequency and the risk of colorectal cancer. To further examine this relationship, we collect the data from cohort studies that make a more accurate estimation. Several online data were searched from inception to February 29, 2020. Ten cohort studies involving 1,038,598 individuals were included in our study. The pooled results indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…According to the analysis, positive family history of CRC, sedentary behavior of more than six hours per day, bowel movements more than once per day, and low educational level were found to be independent predictors of CRC (P = 0.014, P = 0.003, P = 0.036, and P = 0.008, respectively). A person with a positive family history of CRC was 8. included more than one million participants provided strong evidence supporting the association between the frequency of bowel movement and CRC risk [27] . Moreover, a cohort study found that the frequency of bowel movements was associated with an increased risk of rectal cancer but not CRC, and constipation was associated with decreased risks of both CRC and rectal cancer [28] .…”
Section: Independent Predictors Of Crcmentioning
confidence: 85%
“…According to the analysis, positive family history of CRC, sedentary behavior of more than six hours per day, bowel movements more than once per day, and low educational level were found to be independent predictors of CRC (P = 0.014, P = 0.003, P = 0.036, and P = 0.008, respectively). A person with a positive family history of CRC was 8. included more than one million participants provided strong evidence supporting the association between the frequency of bowel movement and CRC risk [27] . Moreover, a cohort study found that the frequency of bowel movements was associated with an increased risk of rectal cancer but not CRC, and constipation was associated with decreased risks of both CRC and rectal cancer [28] .…”
Section: Independent Predictors Of Crcmentioning
confidence: 85%
“…Studies on the association between bowel frequency and CRC risk have not yielded consistent results [ 87 - 90 ]. In a previous meta-analysis of ten cohort studies worldwide, increased frequency of bowel movements was only linked to an increased risk of rectal cancer [ 91 ]. The results were inconsistent among included studies, where a follow-up study in the Chinese population showed that those who had more than one bowel movement per day had an increased risk of CRC within five years of follow-up, while three studies in the USA and one in Japan did not show an association between bowel frequency and CRC risk [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous meta-analysis of ten cohort studies worldwide, increased frequency of bowel movements was only linked to an increased risk of rectal cancer [ 91 ]. The results were inconsistent among included studies, where a follow-up study in the Chinese population showed that those who had more than one bowel movement per day had an increased risk of CRC within five years of follow-up, while three studies in the USA and one in Japan did not show an association between bowel frequency and CRC risk [ 91 ]. Our meta-analysis included two case-control studies and one cohort study, all of which reported a significant positive association between high bowel frequency (more than once per day) and an increased CRC risk among the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…In the process, we found that most of the eQTL were significantly associated with CRC, so we excluded the associated CRC traits to be able to effectively identify other phenotypes associated with them. Several best eQTL-related phenotypes were discovered to be strongly linked or comorbid with the risk of CRC, including bowel movement, alcohol consumption, C-C motif chemokine 22, family history of primary malignant neoplasm, cholelithiasis, and helicobacter pylori infection (Table S5) [14,[37][38][39][40].…”
Section: Summary Data-based Mendelian Randomizationmentioning
confidence: 99%